2007
DOI: 10.1111/j.1600-0714.2007.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of stem cell factor and endothelin‐1 in the emergence of pigmented squamous cell carcinoma in oral mucosa

Abstract: We present here the clinical, morphological and immunohistochemical features of a pigmented squamous cell carcinoma (SCC) in the oral mucosa of the hard palate of a 76-year-old Japanese man. He underwent a partial resection of the maxilla subsequent to radiotherapy. The tumor was typical, moderately well-differentiated SCC but had many melanocytes (melanocytosis) within it. Immunohistochemical analysis for stem cell factor (SCF) and endothelin-1, both of which are known to stimulate proliferation and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…However, the hypothesis that neoplastic cells may produce factors stimulating proliferation and differentiation of melanocytes, such as stem cell factor and endothelin-1, has been proposed (6). The mechanism of colonization of melanocytes in nonmelanocytic tumors, including SCC, is still unknown.…”
Section: Pigmented Cervical Intraepithelial Neoplasiamentioning
confidence: 99%
“…However, the hypothesis that neoplastic cells may produce factors stimulating proliferation and differentiation of melanocytes, such as stem cell factor and endothelin-1, has been proposed (6). The mechanism of colonization of melanocytes in nonmelanocytic tumors, including SCC, is still unknown.…”
Section: Pigmented Cervical Intraepithelial Neoplasiamentioning
confidence: 99%
“…Together these agents account for the melanin pigmentation sometimes observed in association with inflammatory conditions of skin or oral mucosa [41,46], such as oral lichen planus [6] and healing after periodontal surgery [47]. …”
Section: Introductionmentioning
confidence: 99%
“…Satomura et al reported a case of pigmented squamous cell carcinoma of the hard palate. The authors clearly demonstrated stem cell factor and endothelin-1 expression in the neoplastic squamous cells, which may have led to the development of melanocytic colonization in squamous cell carcinoma (11). …”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that the presence of melanocytes may be presented as heterotopic cell rests resulting from aberrant melanocytic migration during the embryonic period (4). It has also been hypothesized that the epithelial cells may produce factors that simulate the proliferation and differentiation of melanocytes, such as stem cell factor and endothelin-1 (11). Satomura et al reported a case of pigmented squamous cell carcinoma of the hard palate.…”
Section: Discussionmentioning
confidence: 99%